SEBUAH UPAYA MERUMUSKAN PEMIKIRAN MORAL KRISTIANI BERWAWASAN GENDER BERHADAPAN DENGAN KDRT - Tejo Sugiarto, B. Ario (P3TK, Sanata Dharma University, 2012)
In social reality, domestic violence is a sadden event that continously happend to women. In gender analysis, gender injustice and patriarchal culture are regarded as the main causal factors of violence against women. From the point of view of women (victims of violence), the Holy Bible is often used to legitimate gender injustice and discrimination against women. For the faithful, this matter has risen a theological dilemma. In one side, this opinion is based on the experiences of the victims. But in another side, the Holy Bible is believed as the Word of God that reveals the Gods will to save human beings (men and women). Therefore, in the context of domestic violence, moral thinking based on gender on christian marriage is really needed.